Caracterização parcial dos efeitos do extrato hidroalcoólico das folhas da Hyptis fruticosa Salzm. (ex) Benth. no sistema nervoso central de camundongos - Cândido, Edna Aragão Farias (2006)
This present study is about the phytotherapic effects of the hydroalchoholic extracted from the Hyptis fruticosa leaves. Typical plant from the northeast of Brazil used as an aromatyzer and discongestyzer. Probably, de Araújo et. al., 1974, were the first ones to study and discribe the studies of the metanolic extracts from the roots of this plant, that contains antimicroorganism and antineoplasic activity. Pain, insomnia and epilepsy are disturbs that attack people in our society, specially pain, causing personal and socialeconomic problems. The main objective of this study is to describe partialy the effects of the hydroalchoholic extracted from the Hyptis fruticosa Salzm. (ex) Benth. leaves in the nervours central system of mice. Having as specifics objectives: to determinate the acute toxicity (DL50); to evidence the anticonvulsant and sedative/hypnotic effects; to mensure the antinociceptive effects in mice. This is an experimental search using acute toxicity test in the doses 1, 2, 3, 4 and 5 grams; pentylenetetrazole-induced convulsion, 60mg/Kg i.p.; pentobarbital-induced sleep, 60mg/Kg i.p.; writhing-induced by acetic acid 6% and tail-flick test. The animals used were the swiss type mice. The data obtained were analysed by ANOVA, the p<0,05 values were considered significant. According to the results, it was demonstrated that the estract has low toxicity; the pentylenetetrazole-induced convulsion showed a latence low increase for the beginning of the 1ª convulsion and the death; The ANOVA showed significance with p<0,0001 at the return of the righting reflex on the sleep-induced by tiopental, writhing-induced by acetic acid and thermal nociceptive stimulation. Is possible to conclude, this way, that the hydroalchoholic extract of Hyptis fruticosa leaves has antinociceptive effects on the central and peripheral nervous system and low sedative, however, without any anticonvulsant activity. For more informations, studies with more details is suggested.